2006
DOI: 10.1002/app.24636
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and electrical properties of polyaniline/CeO2 composites and their application as humidity sensor

Abstract: Polyaniline/CeO 2 composites were synthesized by in situ chemical polymerization method using ammonium persulphate as an oxidizing agent. This is the single step polymerization process for the direct synthesis of emeraldine salt phase of polymer. The polymers were characterized by using FTIR spectral analysis, SEM, and XRD studies. Formation of conducting emeraldine salt phase is confirmed by spectroscopic techniques. High temperature conductivity measurements show ''thermal activated behavior.'' The change in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(36 citation statements)
references
References 30 publications
(27 reference statements)
1
34
0
Order By: Relevance
“…The magnitude of the conductivity is dependent on the number of charge carriers available and their mobility. It has been observed that mobility of charge carriers increases with the increase in temperature leading to the increase in conductivity similar to that reported for PANI/WO 3 and PANI/CeO 2 nanocomposites [22,23]. Another factor which also affects the electrical conductivity is the molecular alignment of the chains within the entire system.…”
Section: Temperature Dependence Of DC Electrical Conductivity Of the supporting
confidence: 76%
See 1 more Smart Citation
“…The magnitude of the conductivity is dependent on the number of charge carriers available and their mobility. It has been observed that mobility of charge carriers increases with the increase in temperature leading to the increase in conductivity similar to that reported for PANI/WO 3 and PANI/CeO 2 nanocomposites [22,23]. Another factor which also affects the electrical conductivity is the molecular alignment of the chains within the entire system.…”
Section: Temperature Dependence Of DC Electrical Conductivity Of the supporting
confidence: 76%
“…1. Significant change in electrical conductivity of the nanocomposite was observed with the rise in temperature; electrical conductivity of PPyZrP increasing with increase in temperature can be explained by ''thermal activated behaviour'' [22]. The conduction mechanism in the conducting polymers is explained in terms of polaron and bipolaron formation.…”
Section: Temperature Dependence Of DC Electrical Conductivity Of the mentioning
confidence: 88%
“…Another factor which also affects the electrical conductivity is the molecular alignment of the chains within the entire system. Parvatikar et al [36,37] have explained the rise in electrical conductivity in their PANI/WO 3 and PANI/CeO 2 nanocomposites on the basis of thermal curing leading to a better alignment of the polymer chains, which increases the conjugation length, and hence an increase in electrical conductivity. Also, molecular rearrangement takes place during heating which makes the molecular conformation favorable for electron delocalization [38].…”
Section: Electrical Conductivity Studiesmentioning
confidence: 97%
“…1. It was observed that the electrical conductivity of the nanocomposite increases with the rise in temperature, which is the characteristics of ''thermal activated behavior'' [36]. To explain the conduction mechanism in the conducting polymers, the concept of polaron and bipolaron was introduced.…”
Section: Electrical Conductivity Studiesmentioning
confidence: 99%
“…Recent investigations have presented that humidity sensors based on CeO 2 powder show poor sensitivity [9], but that a humidity sensor based on CeO 2 nanowires has shown a fast response [10].…”
Section: Introductionmentioning
confidence: 99%